Pharmacological synergism : a multimodal analgesia approach to treat dental pain = Sinergismo farmacológico : un enfoque de analgesia multimodal para el manejo de dolor dental - Chavarría Bolaños, Daniel 1982-
Dental pain is usually managed by clinical interventions and pharmacological coadjuvants such as NSAIDs. However, its perception and modulation is mediated by different nociceptive mechanisms and these strategies can be insufficient. The multimodal analgesia refers to the use of 2 or more analgesic drugs that attenuate or blockade different mechanisms of pain, obtaining a greater clinical effect. Within this concept, pharmacological synergism plays a leading role, combining different molecules in lower doses to diminish also side effects. Since there are no standard prescriptions to be use in all the patients, multimodal approaches allow the clinician to make responsible effective combinations, individualizing analgesia as the pathway to success.